BOOK REVIEW Make Learning Personal: The What, Who, Wow, Where, And Why (Malaysian Management Journal, 2015)
This book is indeed insightful and a challenge to many people who might be complacent in their usual ways of managing teaching and learning. Old habits die hard. For sure, it sounds personal as the title suggests. It resonates with everyoneâ€”you and I; it draws us closer to the heart of the matter, that is, managing how we teach, managing learning, and that matters greatly if we consider the learnersâ€™ perspectives. Barbara Bray and Kathleen McClaskey argue that we should change our â€œperceptions about learning and realize [that] every child is a learnerâ€ (p. xxiii). The idea is, if you are a learner, you ought to be thinking seriously about learning as something you are responsible for, making it your own, if you will. If you are a teacher, you ought to be shifting your paradigm by now; make teaching less centered on you but more on the actual person who is receiving what you teach, the learner. Know your learner, understand what they want and what they think would work for them. The point to drive home is learner-centeredness tends to be the buzz word for the twenty-first century classroom.